Accessible configuration of virtual environments: towards pervasive augmented reality - Cruz, Inês Filipa Mendonça da (2020)
With the present progression of augmented reality in the lives of the everyday person, pervasive augmented reality seems a next logical step for the field to go. There are many technological limitations that prevent pervasive augmented reality from being an actuality, one of them being a lack of tools to easily configure virtual environments without the need of an approach by experts. Consequently, in this dissertation, we developed a approach for the generation, configuration, and visualization of augmented content in real environments. We studied two interaction methods for the placement of virtual objects for augmented reality and assessed the usability of our approach for untrained users.